The power of social media: Exploring online member groups and psychological factors to support responsible consumption - Muchsin Saggaff Shihab; Ridho Bramulya Ikhsan; Ahmad Fakhrorazi (Digital Business, 2025)
Consumer behavior in purchasing green products, especially food and cosmetics, is influenced by many factors. However, the role of online member group support in supporting the purchase of green products has received less attention despite the increase in the number of social media users. With the support of the norm activation model and social learning theory, this study unveils the purchase behavior of green products with the critical factors of social media use, online member group support, and psychological factors. Using a sample of 323 respondents who are experienced in purchasing green products and belong to green communities on social media, structural equation modeling revealed that social media usage and online member group support have a significant influence. Both constructs significantly influence green purchasing behavior. In addition, social media usage significantly influences subjective norms and green knowledge, whereas subjective norms also support green purchasing behavior. Green knowledge contributes to social responsibility, and social responsibility supports green purchasing behavior. This research provides valuable insights for companies on the importance of sustainability innovation for green food and cosmetic products.
Keywords: 650; Consumer social responsibility; Green knowledge; Online member group support; Responsible consumption; Social media usage; Subjective norm